2006
DOI: 10.4269/ajtmh.2006.74.604
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Tuberculosis and Diabetes in the Mexican Border and Non-Border Regions of Texas

Abstract: The association between tuberculosis and underlying risk factors was evaluated in Texas patients hospitalized in the 15 counties along the Mexico border within the remaining non-border counties. A case control analysis of the hospital discharge dataset from the Texas Health Care Information Council was performed for the years 1999-2001. A discharge diagnosis of tuberculosis identified cases (N = 4,915). Deep venous thrombosis, pulmonary embolism, and acute appendicitis conditions identified controls (N = 70,80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 16 publications
2
61
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17] One quarter of the cases of TB in these medically-underserved communities along the Texas-Mexico border were attributable to diabetes. With diabetes on the rise in TB-endemic areas, our findings highlight the re-emerging impact of diabetes, now type 2, on TB control in regions of the world where both diseases are prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13][14][15][16][17] One quarter of the cases of TB in these medically-underserved communities along the Texas-Mexico border were attributable to diabetes. With diabetes on the rise in TB-endemic areas, our findings highlight the re-emerging impact of diabetes, now type 2, on TB control in regions of the world where both diseases are prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 This association (now with type 2 diabetes) was recognized again in the 1990s [6][7][8][9] and is currently supported by a growing body of literature. [6][7][8][9][10][11][12][13][14][15][16][17] According to a recent meta-analysis, diabetes patients have three times the risk of contracting TB as non-diabetics (95% confidence interval, CI: 2.3-4.3) 18 and studies report the fraction of TB cases attributable to diabetes to be between 15% and 25%. 9,13,16 The biological basis for the association between both diseases is not fully understood but studies suggest that diabetes depresses the immune response, which in turn facilitates infection with Mycobacterium tuberculosis and/or progression to symptomatic disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM is a well known risk factor for TB in the past 1,2. Patient with diabetes mellitus type-2 are in particular more prone to getting into infections, including TB, which are more difficult to treat because of their inherent weak immune system, the high prevalence of diabetes could adversely affect global TB control efforts 3,4 . 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes has also been associated with tuberculosis in several studies (5)(6)(7)(8) and has been shown to be a risk factor for severe gram-positive infections (9,10), hospital-acquired postoperative infections (11,12), and urinary tract infections (3).…”
mentioning
confidence: 99%